Evaluation of Colour Preference in Zebrafish for Learning and Memory - Avdesh, A.; Martin-Iverson, M.; Mondal, A.; Chen, M.; Askraba, S.; Morgan, N.; Lardelli, M.; Groth, David; Verdile, G.; Martins, R. (IOS Press, 2012)
There is growing interest in using zebrafish (Danio rerio) as a model of neurodegenerative disorders such as Alzheimer’s disease. A zebrafish model of tauopathies has recently been developed and characterised in terms of presence of the pathological hallmarks (i.e. neurofibrillary tangles and cell death). However, it is also necessary to validate these models for function by assessing learning and memory. The majority of tools to assess memory and learning in animal models involve visual stimuli, including colour preference. The colour preference of zebrafish has received little attention. To validate zebrafish as a model for colour-associated-learning and memory, it is necessary to evaluate its natural preferences or any pre-existing biases towards specific colours. In the present study, we have used four different colours (red, yellow, green and blue) to test natural colour preferences of the zebrafish using two procedures: place preference (PP) and T-maze. Results from both experiments indicate a strong aversion towards blue colour relative to all other colours (red, yellow and green) when tested in combinations. No preferences or biases were found amongst reds, yellows and greens in the place preference procedure. However, red and green were equally preferred and both were preferred over yellow by zebrafish in the T-maze procedure. The results from the present study show a strong aversion towards blue colour compared to red, green and yellow, with yellow being less preferred relative to red and green. The findings from this study may underpin any further designing of colour-based learning and memory paradigms or experiments involving aversion, anxiety or fear in the zebrafish.